(untitled) (Indonesian Tax Justice Review, 2024)
Withholding taxes are a key mechanism for protecting source-based taxing rights in developing countries. This paper analyzes Indonesia’s withholding tax regime on cross-border payments, including interest, royalties, and services. Using doctrinal legal analysis, the study examines how tax treaties and international standards affect revenue outcomes. The findings indicate that treaty limitations significantly reduce source country taxing rights. The global contribution of this paper lies in highlighting structural constraints imposed by international tax agreements on developing countries. Indonesia’s experience offers insights for rethinking treaty policy from a tax justice perspective. The study contributes to global debates on rebalancing taxing rights between residence and source countries.